Performance of Constructed Wetland on the Removal of Nutrient in Domestic Wastewater Using Chrysopogon Zizanioides - Nguyen, My Linh (Journal of Technical Education Science, 2022)
In this study, a native wild plant, Chrysopogon zizanioides (C-zi), was used in a wetland system to treat household wastewater. The root system of the C-zi is comprised of primary roots, secondary roots, and filamentous roots that all extend vertically deep into the soil rather than spreading horizontally. Depending on the concentration of the influent water, the water entering the vetiver-containing tank was stored for 3 to 5 days. These results demonstrated C-superior zi's ability to degrade organic waste as well as nutrients. COD, BOD, phosphorus, and ammonia are all removed with a high degree of effectiveness (82%, 82%, 80%, and 76%, respectively) in both stages of domestic wastewater treatment. The plant's roots had grown from 5 to 30 centimeters in length over the course of three months. In aspects of wastewater treatment and high biomass growth in wetland system, it was proposed that the use of C-zi is favorable.